Village-Owned Enterprise Accounting Based on People's Economy: Against Foreign Hegemonies in Indonesia - Aji Dedi Mulawarman; Virginia Nur Rahmanti; Wilson Junior; Febrina Nur Ramadhani (Yayasan Rumah Peneleh, 2023)
This article aims to initiate village-owned enterprise accounting that is in accordance with the people's economy. This research was conducted in Sungai Pinang Village, Kab. Musi Rawas, South Sumatra. The authors employed Paradigma Nusantara, especially the thought of Nataatmadja as a constructive methodology. The study found that the existence of the village-owned enterprise was not running as well as expected because of the lack of awareness of the responsibility and spirit of the people's economy owned by the local village government in maintaining village sovereignty. The large potential of village revenue that should have been generated from a system of cooperation with foreign factories operating in their government area was lost. This reflects capitalist economic system. Ideally, the existence of village-owned enterprise is not only seen as a formality of completing the mandate of the law but as a means to help each other develop the economic welfare of the community as well as achieving piety.